INSPEKSI TEKNIK STRUKTUR BETON PASCA BAKAR DAN METODE PERBAIKANNYA - Sulardi Sulardi (INFO-TEKNIK, 2018)
The objective of the study was to provide an overview of the inspection method to determine the condition grade and method of improvement on the post-burn concrete chimney reinforced concrete steel structure. Inspection method using visual check method, hammer test compressive strength test and ultrasonic pulse velocity test (UPV Test) method with spontaneous damage condition and light crack. Method of crack repair with material specification of low pressure injection (LPI) method with material specification Resin Concretive 2525 and Resin Barra Emulsion 57, spalling improvement with epoxy grouting method using material flowable microconcrete specification, with good result, as per specification and acceptable. Method of repair of crack injection with epoxy grout method has been registered as a standard working method in PT.Pertamina RU V and can be replicated to overcome similar problems